1996
DOI: 10.1111/j.1365-2958.1996.tb02637.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pufQ‐pufB intercistronic region on puf mRNA stability in Rhodobacter capsulatus

Abstract: Differential expression of genes localized within the polycistronic puf operon of Rhodobacter capsulatus is partly due to altered stabilities of individual mRNA segments. We show that the 5' untranslated region (UTR) of pufB contributes to the unusual longevity of the 0.5 kb light-harvesting (LH) I specific pufBA mRNA and of the 2.7 kb pufBALMX mRNA. Three stem-loop structures have been identified within the pufQ-pufB intercistronic region by means of RNA secondary-structure analysis in vitro and in vivo. Dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 49 publications
(29 reference statements)
1
51
0
Order By: Relevance
“…An alternative model for low-temperature regulation proposes that the decay rate of the lipase-encoding segment of the polycistronic messenger varies with temperature. Differential segmental decay rates have been observed in the case of the puf operon, and furthermore, are subject to regulation by oxygen (Klug, 1991 ;Heck et al, 1996 ;Rauhut & Klug, 1999). Stem-loop structures are known to influence mRNA decay and a number of these have been noted within the intergenic regions of the B52 operon (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative model for low-temperature regulation proposes that the decay rate of the lipase-encoding segment of the polycistronic messenger varies with temperature. Differential segmental decay rates have been observed in the case of the puf operon, and furthermore, are subject to regulation by oxygen (Klug, 1991 ;Heck et al, 1996 ;Rauhut & Klug, 1999). Stem-loop structures are known to influence mRNA decay and a number of these have been noted within the intergenic regions of the B52 operon (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the sRNA and mRNA bands was normalized to the intensity of the 5S or 16S rRNA. Total RNA was isolated by hot-phenol extraction 42 and RNA was stored in 100 μl of 20 mM sodium phosphate (pH 6.5), 1 mM EDTA at -20°C. RNA samples (~30 μg) were denatured for 10 minutes at 65°C in loading buffer containing 50% deionized formamide, separated on urea-polyacrylamide (10%) gels or on a 1% (w/v) agarose 2.2 M formaldehyde gel, and transferred to nylon phase (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Processing of long mRNA by RNA-specific endonuclease( s) and exonuclease(s) has been described or suggested in E. coli and Rhodobacter capsulatus (Belasco et al, 1985 ;Heck et al, 1996;Peterson, 1992;Willison et al, 1993). In this study it was shown (Fig.…”
Section: Aaaacattaatcacaattttat -Atmentioning
confidence: 99%